Respuesta :

Fill in the table using the function rule y= 3x + 5​

________________________________________

Replace each value of x in the expression

____________________________________

x= -4

y = 3* (-4)+5​

= -12 +5

= -7

_______________

x= -2

y = 3* (-2)+5​

= -6 +5

= -1

_____________

x= 0

y = 3* (0)+5​

= 0 +5

= 5

_____________

x= 2

y = 3* (2)+5​

= 6 +5

= 11

______________________________

Answer

_________________________

Can you see the updates?

Do you have any questions regarding the solution?

If you don’t need further explanation on this question, we can end the session.

I want to remind you this answer will always be saved in your profile. I’d really appreciate you letting me know how I did by rating our session after you exit. Thanks and have a great day!

Ver imagen EliavC238763

Otras preguntas

ACCESS MORE